Reconstruction of Supervision of Health Profession Student Practice in Teaching Hospitals Following the Enactment of Law Number 17 of 2023 concerning Health - Henny Susanto; I Gde Sastra Winata (IHSA Institute, 2026)
Regulatory reform through Law Number 17 of 2023 concerning Health brings changes to the system of guidance and supervision of medical and health workers in Indonesia. This change has an impact on the practice of health professions education in teaching hospitals, particularly regarding the mechanism for supervising students involved in clinical services. Legally, health professions students do not yet have the authority to practice independently, but in fact they participate in service actions under supervision. This condition creates a complex legal relationship between students, clinical supervisors, educational institutions, and hospitals, especially when patient safety incidents occur. This study is a normative legal research with a statutory and conceptual approach. Primary and secondary legal materials are analyzed qualitatively through legal interpretation to identify normative gaps and inconsistencies in regulations regarding the supervision of student practice in teaching hospitals. The results show that although Law Number 17 of 2023 concerning Health emphasizes the importance of guidance and supervision of health workers, regulations regarding student practice have not been formulated explicitly. This normative gap has the potential to create legal uncertainty regarding the limits of action authority, supervision standards, and the construction of legal accountability. Therefore, it is necessary to reconstruct supervision by affirming the limits of competence-based authority, strengthening active and documented supervision, and establishing more specific implementing regulations to ensure legal certainty and patient protection.